Inverted internal limiting membrane flap and scleral buckling for retinal detachment with macular hole - Yu-Pei Chen; Yung-Jen Chen (BMC Ophthalmology)
Abstract Background To evaluate anatomical and functional outcomes after vitrectomy with inverted internal limiting membrane flap technique combined with scleral buckling for eyes with rhegmatogenous retinal detachment and a coexisting macular hole. Methods Eleven consecutive patients of primary rhegmatogenous retinal detachment with a coexisting macular hole who underwent vitrectomy with internal limiting membrane flap technique combined with scleral buckling surgery between September 2014 and September 2023 were evaluated retrospectively. The main outcome measurements were the retinal reattachment rate, macular hole closure rate, and final postoperative best-corrected visual acuity. Results The primary retinal reattachment rate and macular hole closure rate were 100% (11/11) after initial surgery. Six patients required secondary surgery to improve vision, including cataract surgery in four patients, combined cataract surgery and silicone oil removal in one patient, and combined epiretinal membrane peeling and silicone oil removal in one patient. Visual acuity improved from 2.45 ± 0.52 logMAR preoperatively to 0.9 ± 0.26 logMAR finally (P = 0.002). However, only one patient (1/11; 9%) demonstrated microstructural recovery on optical coherence tomography (OCT) images. Conclusion Vitrectomy with internal limiting membrane technique combined with scleral buckling achieves favorable anatomical reattachment and macular hole closure rates. The final visual outcomes improve after sequential surgeries. However, as confirmed on OCT, the microstructures did not recover in most cases.